Analisis Ekonomi Efisiensi Operasional Puskesmas dalam Peningkatan Cakupan Layanan Kesehatan Dasar: Pendekatan Teori Efisiensi Farrell dan Metode Frontier Analysis di Kabupaten Bengkalis - Vidia Putri Maharani; Rika Media Elna; Telpa Abdi; Budi Hartono; Alfani Ghutsa Daud (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Community health centers (Puskesmas) play a strategic role as the frontline providers of basic health services in Indonesia. However, variations in operational capacity across units often lead to differences in performance outcomes. This study aims to analyze the operational efficiency of Puskesmas in Bengkalis Regency using Farrell’s Efficiency Theory and Frontier Analysis. A quantitative descriptive-analytic approach was employed, utilizing secondary data on input variables (number of health workers, operational costs, service rooms) and output variables (patient visits, basic immunization coverage, maternal and child health coverage). The results show substantial variation in input allocation and service output across 22 Puskesmas. Only a few units Pakning, Sadar Jaya, and Lubuk Muda achieved high Technical and Economic Efficiency, while others such as Pancur Jaya, Teluk Lecah, and Bengkalis demonstrated low efficiency levels due to high input usage but suboptimal output. These findings emphasize the need for improved planning, resource allocation, and service management to enhance the performance of primary health care facilities.